Coronavirus disease - 2019 pandemic: Strengthening the preparedness of the nations to mount an effective response - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Al Ameen Medical College, 2021)
The coronavirus disease - 2019 (COVID-19) outbreak has become a cause of alarming concern for the public health authorities, since it was first reported in the Wuhan City of China [1]. Since then, as on 18 May 2021, the total of 162184263 cases has been reported across the affected nations and territories, while the infection has accounted for the death of 3364446 individuals due to the disease-associated complications [1-2]. Further, we must note that the virus has been reported in 222 nations and territories, with the American region and the South East Asian Region being the worst affected [1].